A retrospective study of endometrial histopathology in abnormal uterine bleeding patients - Varun, Neha; Gupta, Nidhi; Khan, Sana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Abnormal uterine bleeding (AUB) is one of the most commonly encountered gynecological problem and almost 33 % of women in gynecological outpatient department presented with abnormal uterine bleeding. Dilatation and curettage (D and C) have been the main diagnostic procedure in the evaluation of abnormal uterine bleeding patients for decades. The objective of the present study was to analyze the different types of endometrial histopathology of patients presented with the abnormal uterine bleeding and its correlation with the different types of abnormal uterine bleeding Methods: This is a retrospective study, conducted in a medical college in the Department of Obstetrics and Gynecology over a period of one year from June ’17 to June ’18. All cases of AUB more than 35 years of the age group who underwent D and C procedure were included in this study. Total 100 patients were analyzed. Results: Total 100 patients were analyzed. Age group ranges from 35-58 years and most common age group presenting with AUB was 35-39 years. The most common presenting complaint was menorrhagia 54% (54/100). Histopathology of endometrium showed non-organic causes in 80% (80/100) of AUB patients and the remaining 20% (20/100) had organic causes. Most common endometrial histopathology among non-organic causes was proliferative endometrium 43.75% (35/80) and the most common organic cause was endometrial polyp 40% (8/20). Endometrial hyperplasia was found in 30% (6/20) and endometrial carcinoma was found in 20% (4/20) of cases among organic causes. Conclusions: D and C is the useful and the cost-effective diagnostic procedure in the evaluation of AUB. Histopathological evaluation of endometrial samples is especially indicated in AUB patients to rule out carcinoma and preneoplastic conditions as histopathology is 100% diagnostic in cases of endometrial hyperplasia and carcinoma.